Response to Comment on “Cell nuclei have lower refractive index and mass density than cytoplasm”: A Comment on “How a phase image of a cell with nucleus refractive index smaller than that of the cytoplasm should look like?”, e201800033 - Mueller, Paul; Guck, Jochen (Journal of Biophotonics, 2018)
In a recent study entitled “Cell nuclei have lower refractive index and mass density than cytoplasm,” we provided strong evidence indicating that the nuclear refractive index (RI) is lower than the RI of the cytoplasm for several cell lines. In a complementary study in 2017, entitled “Is the nuclear refractive index lower than cytoplasm? Validation of phase measurements and implications for light scattering technologies,” Steelman et al. observed a lower nuclear RI also for other cell lines and ruled out methodological error sources such as phase wrapping and scattering effects. Recently, Yurkin composed a comment on these 2 publications, entitled “How a phase image of a cell with nucleus refractive index smaller than that of the cytoplasm should look like?,” putting into question the methods used for measuring the cellular and nuclear RI in the aforementioned publications by suggesting that a lower nuclear RI would produce a characteristic dip in the measured phase profile in situ. We point out the difficulty of identifying this dip in the presence of other cell organelles, noise, or blurring due to the imaging point spread function. Furthermore, we mitigate Yurkin's concerns regarding the ability of the simple-transmission approximation to compare cellular and nuclear RI by analyzing a set of phase images with a novel, scattering-based approach. We conclude that the absence of a characteristic dip in the measured phase profiles does not contradict the usage of the simple-transmission approximation for the determination of the average cellular or nuclear RI. Our response can be regarded as an addition to the response by Steelman, Eldridge and Wax. We kindly ask the reader to attend to their thorough ascertainment prior to reading our response.
CRIS-Team Scopus Importer:2022-08-05
Keywords: optical diffraction tomography; quantitative phase imaging; refractive index; simple-transmission approximation